GLUT1 inhibition by BAY-876 induces metabolic changes and cell death in human colorectal cancer cells - Masato Hayashi; Keishi Nakamura; Shinichi Harada; Mariko Tanaka; Akiko Kobayashi; Hiroto Saito; Toshikatsu Tsuji; Daisuke Yamamoto; Hideki Moriyama; Jun Kinoshita; Noriyuki Inaki (BMC Cancer)
Abstract Background Glucose transporter 1 (GLUT1) is known to play a crucial role in glucose uptake in malignant tumors. GLUT1 inhibitors reportedly exhibit anti-tumor effects by suppressing cancer cell proliferation. BAY-876, a selective GLUT1 inhibitor, has been shown to inhibit tumor growth in ovarian and breast cancers. In this study, we investigated the anti-proliferative effects of BAY-876 treatment in human colorectal cancer (CRC) cell lines. Methods We investigated the metabolic changes and effects on proliferation from BAY-876 treatment in HCT116, DLD1, COLO205, LoVo, and Caco-2 cells in vitro. Additionally, a mouse xenograft model was established using HCT116 cells to examine the tumor-inhibitory effects of BAY-876 treatment in vivo. Results BAY-876 treatment inhibited cell proliferation in HCT116, DLD1, COLO205, and LoVo cells. Reduced GLUT1 protein expression levels were observed through western blot analysis. Flux analysis indicated enhanced mitochondrial respiration, accompanied by increased reactive oxygen species levels and apoptosis rates. Tumor-inhibitory effects were also observed in the xenograft model, with the BAY-876-treated groups showing GLUT1 suppression. Conclusions BAY-876 treatment induced metabolic changes and inhibited cell proliferation in human CRC cell lines. Using BAY-876 is a potential novel approach for treating CRC.